2022
DOI: 10.1371/journal.pone.0267157
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of pain neuroscience continuing education on physical therapy outcomes for patients with low back and neck pain

Abstract: Objectives Research suggests that attendance by physical therapists at continuing education (CE) targeting the management of low back pain (LBP) and neck pain does not result in positive impacts on clinical outcomes. The aim of this study was to determine if therapists attending a self-paced 3-hour online Pain Neuroscience Education (PNE) program was associated with any observed changes to patient outcomes and also clinical practice. Methods Participants were 25 different physical therapists who treated 3,70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Of 787 non‐duplicated citations identified in the literature, 19 were further analysed to confirm their eligibility. Twelve were excluded after full‐text reading: four as they included participants with concurrent low back pain (Bilterys et al, 2022; Malfliet, Kregel, Coppieters, et al, 2018; Malfliet, Kregel, Meeus, Roussel, et al, 2018; Van Bogaert et al, 2021), two for not being RCTs (Jessica Van Oosterwijck et al, 2011; Louw et al, 2022), one for not reporting pain intensity and kinesiophobia (Willaert et al, 2020), two for lacking control groups and not using PNE (Brage et al, 2015; Ris et al, 2016), two for using the bio‐behavioural approach instead of PNE (Beltran‐Alacreu et al, 2015; López‐de‐Uralde‐Villanueva et al, 2018), and one for having participants overlapping with another publication by the author (Neto et al, 2018). The reasons for exclusion are listed in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Of 787 non‐duplicated citations identified in the literature, 19 were further analysed to confirm their eligibility. Twelve were excluded after full‐text reading: four as they included participants with concurrent low back pain (Bilterys et al, 2022; Malfliet, Kregel, Coppieters, et al, 2018; Malfliet, Kregel, Meeus, Roussel, et al, 2018; Van Bogaert et al, 2021), two for not being RCTs (Jessica Van Oosterwijck et al, 2011; Louw et al, 2022), one for not reporting pain intensity and kinesiophobia (Willaert et al, 2020), two for lacking control groups and not using PNE (Brage et al, 2015; Ris et al, 2016), two for using the bio‐behavioural approach instead of PNE (Beltran‐Alacreu et al, 2015; López‐de‐Uralde‐Villanueva et al, 2018), and one for having participants overlapping with another publication by the author (Neto et al, 2018). The reasons for exclusion are listed in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Although our study found no statistically significant association between the groups, we concur with the literature that psychological screening is required to guide better patient selection, and if needed psychological treatment prior to SCS trial and implantation is necessary to reduce confounding variables to SCS response. Pain neuroscience patient education and treatment on psychological factors have been associated to improve chronic pain, disability, and multidisciplinary treatment outcomes prior to surgical interventions 82,83 …”
Section: Discussionmentioning
confidence: 99%
“…Pain neuroscience patient education and treatment on psychological factors have been associated to improve chronic pain, disability, and multidisciplinary treatment outcomes prior to surgical interventions. 82,83 History of spinal surgery…”
Section: History Of Psychiatric Illnessmentioning
confidence: 99%
“…They also tend to employ less provocative biomedical language and approaches when addressing pain, adjust their clinical practices to better treat individuals in pain, and ultimately achieve better patient outcomes. 13,32,33 Second, and perhaps of greater significance, studies have demonstrated that enhancements in pain knowledge among patients have a beneficial impact on various aspects including self-reported pain ratings, disability, fear and fear-avoidance, pain catastrophizing, willingness and ability to move, as well as healthcare expenditures. [7][8][9] For athletes this is very important, since pain, fear and catastrophizing all have the potential to impact movement, performance, motor control, concentration, which are essential for optimial performance.…”
Section: Brain Processingmentioning
confidence: 99%